4 The occurrence of lateral ankle sprains in collegiate athletes with and without chronic ankle instability. (12th October 2015) - Docherty, CL; Simon, JE; Donahue, M; Hall, E
Abstract : Background: Lateral ankle sprains occur at a high rate in competitive athletics. Following an ankle sprain, residual symptoms and recurrent injuries often persist. This can lead to chronic ankle instability (CAI) and eventually osteoarthritis. Therefore, understanding the magnitude of these long term issues is critically important to healthcare providers. Objective: To determine the prevalence of CAI in Division I college athletes and any potential relationship between the presence of CAI and subsequent ankle sprain occurrence. Design: Case-control study. Setting: Division I Athletics Department. Participants: A total of 462 college athletes participated in this study (184 males, 278 females, age = 19.5 ± 1.3 years, height = 178.4 ± 0.7 cm, body mass = 73.7 ± 10.5 kg). All participants completed the Identification of Functional Ankle Instability (IdFAI) survey to determine presence of CAI. Individuals scoring ≥11 on the IdFAI were classified as having CAI, and those scoring <11 as not having CAI. Interventions: Frequency of ankle injury along with descriptive information (e.g. side, grade, etc…) was tracked for all participants for an academic year. Main outcome measurements: Frequency of ankle sprains. A non-parametric c 2 test of independence was used to determine the presence of an association between CAI status and subsequent ankle sprain occurrence. A priori alpha was set a p < 0.05.  Results: Of the athletes included in this study, 40.5% (n = 187) had CAI. Of all 462 athletes there were 58 athletes who sustained an ankle sprain during the academic year; of those 58 ankle sprains 35 (60.3%) were identified as having CAI at the beginning of the study. There was a significant association between CAI status and the presence of sustaining an ankle injury during the academic year (c 2 (1) = 10.9, p = 0.001). Conclusions: Similar to previously published results, there is a high prevalence of CAI in collegiate athletes. These data provide support that athletes with CAI have a significant association with sustaining an ankle sprain during the athletic season.